Trends in smoking during pregnancy by socioeconomic characteristics in the United States, 2010-2017 - Sunday Azagba; Lauren Manzione; Lingpeng Shan; Jessica King (BMC, 2020)
Abstract Background Maternal smoking during pregnancy remains a public health concern in the United States (US). We examined whether the prevalence of smoking during pregnancy decreased between 2010 and 2017 and how trends differed by demographic subgroups. Methods We used 2010-2017 data from the National Center for Health Statistics. Rao-Scott Chi-Square tests were performed to compare characteristics between smoking and nonsmoking groups. Cochran-Armitage tests and logistic regression were used to assess overall changes in the prevalence of smoking during pregnancy over time and changes for age, race, and educational attainment subgroups. Results The prevalence of smoking during pregnancy decreased from 9.2% in 2010 to 6.9% in 2017. In 2017, the prevalence was highest among women aged 20-24 (9.9%), American Indian/Alaskan Natives (15%), and those with a high school diploma or General Educational Development (GED) (12.2%). The prevalence was lowest among women younger than 15 (1.7%), Asian/Pacific Islanders (1%), and those who had a master's degree and higher (0.3%). Prevalence did not decrease significantly over time in the 35-39 age group (4.5 to 4.4%; p = 0.08), and increased dramatically for women with less than a high school diploma from 10.2 to 11.8%; p < 0.0001. Conclusions Smoking prevalence during pregnancy in the US is declining, but is highest among younger women (20-24), American Indian/Alaska Natives, and women with a high school diploma or GED. In addition, the prevalence has increased for women with the least education. Targeted research and tobacco control interventions could help address the specific needs of these high-risk subpopulations.